Religious Iconography in Digital Media: Analyzing its Influence on the Untouchable Society - Nurdin, Ali; Ilaihi, Wahyu (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
This study aims to explain the tendency of religious discussions carried out by grassroots communities 'untouched by online media' in the southern region of East Java. This research employs a quantitative approach to measure the tendencies of grassroots communities in Southern East Java regarding beliefs, practices, experiences, knowledge, and expectations of reward consequences. The study focuses on the regions of Malang, Trenggalek, Lumajang, and Blitar. Data collection was conducted through semi-open interviews with 40 purposively selected respondents. Data analysis utilized descriptive statistics to explain the trends in religious communication within these communities. The findings indicate that the propensity to engage in discussions about religious beliefs is intricately connected to topics such as the Oneness of God, appeals for assistance, concepts of destiny, the nature of Allah, and the interplay between religion and government. The highest score for religious communication is associated with discussions on the Oneness of God, which reached 82.50%. Examining tendencies related to religious knowledge and practices includes topics such as prayer, zakat (obligatory charity), fasting, Hajj, and approaches to attaining closeness to Allah, with prayer services achieving a significant score of 77.50%. In the analysis of religious experiences encompassing Islamic teachings, virtuous behaviors, immoral conduct, and individual experiences, the highest recorded score is 72.50%. The results reveal that discourse surrounding cooperation in righteousness is the most prevalent form of religious communication within grassroots communities, attaining a score of 90.00%. The emphasis on the Oneness of God and the observance of prayer services also underscores the community's commitment to core religious beliefs and practices.